The Structure Analysis of Secondary (Recycled) AlSi9Cu3 Cast Alloy with and without Heat Treatment - Lenka HURTALOVÁ; Eva TILLOVÁ; Maria CHALUPOVÁ (Engineering Transactions)
Al-Si alloys are very universal materials, comprising of from 85% to 90% of the aluminium cast parts produced for the automotive industry (e.g. various motor mounts, engine parts, cylinder heads, pistons, valve retainer, compressor parts, etc.). Production of primary Al- alloys belong to heavy source fouling of life environs. Care of environment of aluminium is connected to the decreasing consumption of resource as energy, materials, water, and soil, and with an increase in recycling and extension life of products in industry. Recycled (secondary) aluminium alloys are made out of Al-scrap and workable Al-garbage by recycling. The automotive casts from aluminium alloys are heat treated for achieving better properties. Al-Si alloys contain more addition elements, that form various intermetallic phases in the structure. They usually contain a certain amount of Fe, Mn, Mg, and Zn that are present either unintentionally, or they are added deliberately to provide special material properties. These elements partly go into the solid solution in the matrix and partly form intermetallic particles during solidification which affect the mechanical properties. Controlling the microstructure of secondary aluminium cast alloy is therefore very important.